Multitafsir Pemaknaan Kata “Nonfisik” Pasal 5 Uu TPKS: Studi Komparatif Indonesia - Filipina - Fatikha Adinda Widia Putri; Lutfillah Arrizqi Zainsyah (Indonesian Journal of Criminal Law, 2025)
Technological developments have expanded the scope of sexual harassment, with social media becoming a new gateway for criminal acts of harassment. The Criminal Code and the Electronic Information and Transactions Law establish a normative framework for indecency offenses; however, these regulations fail to encompass non-physical sexual harassment in the digital domain. The TPKS Law, which should serve as the primary legal framework for addressing sexual harassment, has instead given rise to multiple interpretations of Article 5. This article appears to be biased in its provision of legal certainty, potentially leading to variations in the criminal liability of perpetrators. This study aims to identify the differences between Indonesian and Philippine criminal law regarding the limitations and sanctions for non-physical harassment, as well as to determine the extent to which the legal conceptions of the two regulations overlap. The research employs a normative juridical method, utilizing a comparative, legislative, and conceptual approach. The results indicate that there are disparities between the two countries, with Indonesia lagging far behind the Philippines in terms of substance. Therefore, Indonesia needs to strengthen its regulations on non-physical sexual harassment, especially in the digital realm, to close this gap.